The Green School Concept in Elementary Schools as an Effort to Form Sustainable Behavior and Environmental Awareness - Khofi, Mohammad Bilutfikal (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Green schools address "nature-deficit disorder" by creating an environment that supports children's interaction with nature. This concept should be implemented since elementary school to form a generation that cares about the environment, is healthy, and is ready to face sustainability challenges. The main objective of this study is to find an effective sustainability education strategy that supports environmental-based education practices in green schools and a learning environment that supports environmental awareness and sustainability. This study uses the Systematic Literature Review (SLR) method to identify, review, evaluate, and interpret relevant research. Researchers conducted a literature search in Pubmed, Garuda, Google Scholar, Scopus, and Springer Link with the keywords "sustainability education," "environmental education practices," and "green schools." Articles were selected based on inclusion criteria, namely focusing on sustainability education and environmental-based practices in green schools and having relevant empirical data. Articles that met the criteria were analyzed to identify trends, challenges, and practical strategies for implementing sustainability education. The results highlight that Green Schools significantly contribute to academic performance, environmental awareness, and the development of pro-environmental behaviors. Practical implementations, such as project-based learning activities like recycling projects and school gardening, enhance students' engagement with sustainability topics. This research underscores the importance of adopting Green School practices at the elementary level as a long-term investment in creating environmentally responsible future generations.